154k views
3 votes
The solution to 9(x+2) = 5 - 2(x - 1) is
*Show your work*

User K F
by
4.5k points

2 Answers

6 votes

Answer:

x = -1

Explanation:

9(x+2) = 5 - 2(x-1)

9(x+2) = 5 - 2(x - 1)

9x+18 = 5-2x+2

9x+18 = -2x+7

+2x +2x

11x + 18 = 7

-7 -7

11x + 11 = 0

-11 -11

11x = -11

x = -1

User Justin Herrick
by
4.5k points
3 votes

Answer:

x=-1

Explanation:

9(x+2) = 5 - 2(x - 1)

9x+18 = 5-2x+2

9x+18 = -2x+7

+2x = +2x +7

-----------------------

11x+18 = 7

-18 = -18

-----------------------

11x = -11

÷11 = ÷11

-----------------------

x = -1

User Asetti Sri Harsha
by
4.9k points